Legal Certainty of the Application of Electronic Signatures in the Creation of Notarial Authentic Deeds - Erlim Saat; Dewi Iryani; Gradios Nyoman Tio Rae (Fakultas Syariah IAIN Langsa, 2026)
In modern legal frameworks, the application of electronic signatures should enhance legal certainty, expedite the preparation of notarial authentic deeds, and provide maximum protection for the parties involved. In reality, digital notary practices in Indonesia still face legal uncertainty, regulatory disharmony among the Notary Law (UUJN), Electronic Information and Transactions Law (UU ITE), Government Regulation on Electronic Systems and Transactions (PP PSTE), and the Civil Code (KUH Perdata), as well as technical and procedural implementation limitations that may give rise to potential legal disputes. This study aims to analyze the regulation of electronic signatures and authentic deeds within the framework of Indonesian positive law, assess legal strength, effectiveness, and challenges in implementing Cyber Notary, and explore regulatory disharmonies. The research employs a normative legal method with a qualitative approach, utilizing primary and secondary legal materials and interviews with notary practitioners. The findings highlight the need for regulatory harmonization, strengthened procedures and digital governance, and the development of clear implementation guidelines to ensure effective, secure, and legally certain digital notary practices in Indonesia.